2015
DOI: 10.18438/b8zc88
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Visible Minority Librarians in Canada: A National Survey

Abstract: Objective -This paper is based on a national survey conducted in late 2013 by the authors, then co-moderators of the Visible Minority Librarians of Canada (ViMLoC) Network of the Canadian Library Association (CLA). It is a first survey of its kind, aiming to capture a snapshot of the demographics of the visible minority librarians working in Canadian institutions. The authors hoped that the data collected from the survey and the analysis presented in this paper would help identify the needs, challenges and bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Other factors influencing job satisfaction for visible minority librarians were different from those found in studies of librarians in general. These included a concern over the lack of diversity within their organizations, leading to feelings of isolation (Kumaran & Cai, 2015;Preston, 1998;Thornton, 2000). Some studies reported discrimination and racism at work, and found that higher levels of support for workplace diversity and equity, and sensitivity to the challenges faced by visible minority librarians led to greater job satisfaction (Kandiuk, 2014;Preston, 1998;Thornton, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors influencing job satisfaction for visible minority librarians were different from those found in studies of librarians in general. These included a concern over the lack of diversity within their organizations, leading to feelings of isolation (Kumaran & Cai, 2015;Preston, 1998;Thornton, 2000). Some studies reported discrimination and racism at work, and found that higher levels of support for workplace diversity and equity, and sensitivity to the challenges faced by visible minority librarians led to greater job satisfaction (Kandiuk, 2014;Preston, 1998;Thornton, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Professional associations such as the American Library Association have developed standards for diversity in libraries, track diversity statistics, and offer scholarship and residency programs to encourage greater numbers of racialized or visible minority librarians in the profession. A growing professional literature explores the workplace experiences of minority groups within librarianship, including a number of recent studies that raise awareness and attempt to address equity concerns in Canadian librarianship (Hudson, 2017;Kandiuk, 2014;Kumaran & Cai, 2015). There appears to be increasing awareness of and attention paid to equity concerns within the profession.…”
Section: Introductionmentioning
confidence: 99%
“…The first National Survey of Visible Minority Librarians reported that at least 120 librarians identified as visible minorities in 2014. 7 There was an upward trend in hiring visible minority librarians over a decade. 8 The 8Rs Institutional Survey showed that visible minority librarians increased their representation rate from 5 percent in 2003 to 11 percent in 2013.…”
Section: Representation Of Visible Minorities In Canadian Librariesmentioning
confidence: 99%
“…But we also know that racial fears underpin many of the claims of unsafety at Millennium. It is a space where patrons are likely to be Indigenous or newcomers, while library workers are overwhelmingly white settlers from higher socioeconomic brackets (Galvan, 2015;Honma, 2005;Hudson, 2017;Kumaran & Cai, 2015;Schmidt, 2019a). This tension and the narrative of violence coming from particular sources create racial discomfort, but discomfort is not the same as being unsafe (DiAngelo, 2018).…”
Section: Rationalementioning
confidence: 99%